Planning Optimization of a Standalone Photovoltaic/Diesel/Battery Energy System for a Gold Mining Location in Mauritania - Salihi, Kebbada; Taha, Mohammed Qasim; Oubeidi, Abdou; Ndongo, Mamoudou; Jabrallah, Sadok Ben; Heiba, Bamba El (Engineering, Technology & Applied Science Research, 2024)
The greenhouse gas emissions resulting from the excessive use of Diesel Generators (DGs) in mining locations pose a threat to the environment and the macroeconomic sustainability of this industry. This paper aims to decrease or eliminate the use of DG units in gold mining areas to increase access to more clean Renewable Energy Sources (RESs) such as Photovoltaic (PV) systems. In order to evaluate PV potential at small-scale gold mining sites in Mauritania, ArcGIS software is utilized to analyze Chagatt gold mining location as a case study. The techno-economic viability of a PV/DG/battery Hybrid Energy System (HES) was examined and discussed. For yearly modeling, the PVsyst and HOMER Pro were employed to assess the performance of the ideal size of HES in terms of installation and energy costs. The findings indicate that Mauritania's gold mining locations are most suitable for PV energy harvesting. As a result, this industry may rely on clean PV energy.